The greatest challenge in contemplative science: tailoring meditative practices - Javier Garcia-Campayo; Roberto Whyte; Rinchen Hijar-Aguinaga (Frontiers in Psychology)
The practice of meditation has grown in popularity around the world in recent decades. However, standard and untailored meditative practices are recommended for all practitioners, regardless of their personality traits or characteristics. No scientific attempts have been made to match specific meditation types with personality. This paper summarizes the limited proposals relevant to this subject in contemplative traditions such as Buddhism and schools of humanistic and transpersonal thought, including the Enneagram. We also discuss future research directions in this field.